2002
DOI: 10.1210/jc.87.3.1111
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Developmental Competence of Oocytes in Adult Prenatally Androgenized Female Rhesus Monkeys Undergoing Gonadotropin Stimulation for in Vitro Fertilization

Abstract: To determine whether prenatal T propionate exposure beginning gestational d 40-44 (early-treated) or 100-115 (late-treated) affects oocyte competence, five early-treated and five late-treated prenatally androgenized and five normal monkeys underwent recombinant human FSH injections with oocyte-retrieval after hCG administration. Serum FSH, LH, estradiol (E(2)), progesterone (P(4)), androstenedione (A(4)), T, and dihydrotestosterone were measured basally, during gonadotropin stimulation and at oocyte-retrieval;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(83 citation statements)
references
References 0 publications
3
76
0
4
Order By: Relevance
“…It has been demonstrated that typically increased LH in PCOS patients suppressed FSH function, promoting premature granulose cells luteinization and follicular atresia in small antral follicles [25][26][27], which all impaired the quality of both oocyte and embryo [28,29]. Indeed, LH levels on day 3 before starting GnRH agonist medication were significantly increased in the high AMH group,and regression analysis indicated LH level was the only independent predictor of IR in our study, so the mostly elevated LH may be contribute to the decreased embryo developmental competence and consequently declined IR in the high AMH group.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that typically increased LH in PCOS patients suppressed FSH function, promoting premature granulose cells luteinization and follicular atresia in small antral follicles [25][26][27], which all impaired the quality of both oocyte and embryo [28,29]. Indeed, LH levels on day 3 before starting GnRH agonist medication were significantly increased in the high AMH group,and regression analysis indicated LH level was the only independent predictor of IR in our study, so the mostly elevated LH may be contribute to the decreased embryo developmental competence and consequently declined IR in the high AMH group.…”
Section: Discussionmentioning
confidence: 99%
“…Adiposity-related effects on intrafollicular insulin concentration also might harm the oocyte because exposure of murine cumulus-oocyte complexes to insulin causes LH receptor up-regulation and reduced blastocyst development (38). Moreover, premature follicle luteinization and impaired oocyte competence accompany relative insulin excess in prenatally androgenized female rhesus monkeys undergoing gonadotropin therapy for IVF (39). In this regard, increased intrafollicular insulin concentrations were present in our women with impaired glucose tolerance, most of whom were obese, and might be responsible for the reduced fecundity previously reported in such individuals (40).…”
Section: Discussionmentioning
confidence: 99%
“…All hormones were assayed in the WPRC Hormone Assay Services Laboratory (40, 49,50). Circulating levels of total free fatty acids (51), and glycosylated hemoglobin (52) were assayed, as previously described.…”
Section: Assay Proceduresmentioning
confidence: 99%